The Development of Learner Quality on Achievements by the 6A Process of Ban Kham School Under the Sakon Nakhon Primary Educational Service Area Office 3 - Seemakam, Danprai (Interdisciplinary Academic and Research Journal, 2022)
The government has set up educational policies to accelerate the quality of education to increase learning achievement at all levels, as measured by passing national and international standardized tests, which Thai society and the Ministry of Education are giving priority. In the beginning and in trying to improve the quality of education, all educational institutions need to build confidence in a society that they can provide a quality education that meets the expectations of society. Thus, the research aims : (1) to study the process of improving learner quality in terms of learning achievement, (2)to study the operating conditions according to the process of developing learners’ quality in terms of learning achievement, (3) establish and develop the process of developing learners' quality in terms of learning achievement, and (4) to study the results of an experiment in using the process of developing learners' quality in terms of learning achievement. This research was conducted at Ban Kham School under Sakon Nakhon Primary Educational Service Area Office 3. The data resources from the study of documents and related research are used as guidelines for defining research concepts, creating data collection tools, as well as creating and developing processes for improving the quality of learners in terms of learning achievement. This research is Research & Development divided into 4 phases as follows: (1) Phase 1 studied the process of developing learner quality in terms of learning achievement. (2) Phase 2 is to study the operational conditions according to the process of developing learners' quality in terms of learning achievement. (3) Phase 3: Build and develop the process of developing learners' quality in terms of learning achievement. And Phase 4 is to study the results of an experiment using the process of improving learner quality in terms of learning achievement. The research results found that: (1) The process of improving the quality of learners in terms of learning achievement consists of 6 steps: (a) Analysis of basic data to improve learner quality. (b) goal setting and achievement of learner quality development. (c) Raising awareness and participation to improve learner quality. (d) teaching and learning management. (e) Supervision, supervision, monitoring, and evaluation. And (f) the organization of supplementary activities to improve the quality of learners. All 6 steps were appropriate according to the opinions of 5 experts, overall, at the highest level. (2) The operating condition according to the process of improving the quality of learners in terms of overall learning achievement is at a moderate level. When considered step by step, it was found to be at a moderate level at every step, where the highest average step is to set goals and achieve learner quality development, followed by supervision, monitoring, and evaluation. The lowest mean component was teaching and learning. (3) The process of developing learner quality in terms of learning achievement at Ban Kham School under the Office of Sakon Nakhon Primary Educational Service Area 3 is a process 6A consisting of A1 (Analysis) Basic data analysis to improve learner quality. A2 (Aims) goal setting and achievement of learner quality development. A3 (Awareness) Raising awareness and participation to improve learner quality. A4 (Active Learning) Proactive learning management. A5 (Assessment) Assessment to improve learner quality. And A6(Addition) knowledge enhancement. The process of improving the quality of learners in terms of learning achievement was appropriate according to the opinions of the 5 experts as a whole at the highest level. And (4) The results of the experiment on the process of developing learners' quality in terms of learning achievement found that the average academic achievement score of grades 1-6 students including 8 learning subject groups in the academic year 2021 increased by 12.74% from the academic year 2020. The average score of the Reading Test (RT) grade 1 overall in the academic year 2021 increased from the academic year 2020 by an average of 7.47 percent. The average score of National Test (NT) grade 3 overall in the academic year 2021 increased from the academic year 2020 by an average of 61.24%. The average score of the Ordinary National Education Test (O-NET) Grade 6 overall, the academic year 2021 was 16.59 percent higher than that of the 2020 academic year.